2019
DOI: 10.1021/acsphotonics.8b01553
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Enhancement of Electroluminescence from Highly Strained Germanium Light-Emitting Diodes

Abstract: The full exploration of Si-based photonic integrated circuits is limited by the lack of an efficient light source that is compatible with the complementary metal− oxide−semiconductor process. Highly strained germanium (Ge) is a promising solution, as its band structure can be fundamentally altered by introducing tensile strain. However, the main challenge lies in the incorporation of an electrical structure while maintaining high strain with uniform distribution in the active region. Here we present highly str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The gap between the cutter and the bottom tray is set to be 150 μm so that the chip does not break after dicing. The protecting layer can avoid electrochemical corrosion during the wet etching process [29]. The TMAH solution eats off the Si material through the microbridge window and forms suspended microbridge structure as the solution has a high selection ratio for Si material [30][31][32].…”
Section: Design and Fabricationmentioning
confidence: 99%
“…The gap between the cutter and the bottom tray is set to be 150 μm so that the chip does not break after dicing. The protecting layer can avoid electrochemical corrosion during the wet etching process [29]. The TMAH solution eats off the Si material through the microbridge window and forms suspended microbridge structure as the solution has a high selection ratio for Si material [30][31][32].…”
Section: Design and Fabricationmentioning
confidence: 99%
“…Germanium (Ge) has been one of the most attractive candidates for near-infrared (NIR) applications because of its high absorption coefficient, high mobility, and inherent compatibility with complementary metal oxide semiconductor technology. In addition, the indirect band gap structure of Ge can be transited to direct by tensile strain, leading to enhanced optoelectronic performance . For example, Kim et al demonstrated flexible NIR Ge PDs based on a metal–semiconductor–metal (MSM) configuration .…”
Section: Introductionmentioning
confidence: 99%
“…However, this poses challenges of electrical interconnections between Si CMOS circuits and the strained materials. The limited number of reports of opto-electronic devices on these strained mate stage for PIC in large devic the other hand with a compr there have a engineering [ remains challe In this wo structure to b erials [13][14][15] a integration. A ce footprint (d , abandoning romised magni also been stu 18,19].…”
Section: Introductionmentioning
confidence: 99%